Guidebook for environmental and natural resources accounting methods and procedures. ([Quezon City] Department of Environment and Natural Resources, 1993)
A manual on resource accounting to aid policymakers, students, researchers and advocates for Philippine natural resources. Includes definition of terms, physical account procedures, valuation methods, data requirements and sample computations. Also refer to "Guide to Environmental Accounting and Policy Development: The ENRAP Experience" for a more detailed explanation of the framework and policy applications governing this work.
I. Introduction: What are the objectives of the ENRA guidebook? -- What does it contain? II. Environmental waste disposal services: Definition --Quantification -- Air -- Area sources -- Mobile sources -- Stationary point sources -- Water -- Domestic effluents -- Surface runoff -- Industrial wastewater --Valuation -- Principles -- Approaches and procedure -- Application: Mobile source (air) -- III. Environmental damages: Definition-- Valuation methods for environmental impacts analysis -- Generally applicable techniques -- Selectively applicable techniques -- Potentially applicable techniques -- Health damages -- Quantification -- Approaches -- Applications -- Data requirements and sources -- Valuation -- Approaches used By ENRAP -- Applications -- Data requirements and sources -- Nonhealth impacts -- Quantification and valuation methods -- Approaches -- Applications -- Data requirements and sources -- IV. Direct nature services: Definition -- Valuation methods -- Application: visit to national forest parks -- V. Economic depreciation of natural resources: Physical accounting basics -- Valuation methods -- Repetto or net rent approach -- El Serafy approach -- Change in asset value (or present value) approach -- Applications -- Net price approach: as applied to forest resources (renewable) -- El serafy approach: as applied to mineral resources (non-renewable) -- Asset value approach -- Change in asset value approach: as applied to forest resources -- Change in asset value approach: as applied to fishery resources -- Change in asset value approach: as applied to soils resources (semi-renewable) -- VI. Unmarketed household production: Components -- Valuation methods and estimation procedure -- Data requirements and sources.
At head of title: Philippine Environmental and Natural Resources Accounting Project (ENRAP)
"Prepared for the Department of Environment and Natural Resources by the International Resources Group in association with Edgevale Associates and the Resources, Environment and Economics Center for Studies, Inc. under contract no. 492-0465-C-00-4042-00 with the United States Agency for International Development (USAID/Philippines)." --Title page.
Includes bibliographical references.
Keywords: Environmental auditing -- Philippines -- Handbooks, manuals, etc; Natural resources -- Accounting -- Philippines